EXPLORING AUDIT COMPLEXITIES: KEY FACTORS SHAPING FRAUD DETECTION SKILLS - Sari, Hotma Glorya Ika; Wicaksono, Dading Damas Ario; Aritonang, Astri Yunita (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2025)
This study investigates the interplay between auditor workload, auditor experience, professional skepticism, and fraud detection in Indonesian public accounting. Given the increasing complexity of audits and the prevalence of fraud, the research aims to explore how these factors impact auditors' ability to identify fraudulent activities. Based on survey data from 250 auditors, the findings reveal that high workloads negatively impact fraud detection capabilities, whereas experience and professional skepticism positively contribute to detection effectiveness. Additionally, professional skepticism moderates the negative impact of workload on fraud detection but may weaken the positive effect of experience. These findings underscore the importance of effective workload management and the development of professional skepticism to enhance fraud detection. Recommendations include equitable workload distribution, on going training to foster skepticism and analytical skills, and technology integration in auditing. These findings provide valuable insights for practitioners, fostering a proactive approach to fraud prevention and contributing to greater accountability and transparency in financial practices.